2018
DOI: 10.1016/j.jtumed.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism and its associated factors after radioactive iodine therapy among patients with hyperthyroidism in the Northeast Coast State of Malaysia

Abstract: Objectives The aim of this study was to determine the incidence of hypothyroidism and its associated factors within one-year post radioactive iodine (RAI) therapy. Methods A retrospective study was conducted among patients with hyperthyroidism who received RAI therapy at Nuclear Medicine Clinic, Hospital Universiti Sains Malaysia (HUSM), Kelantan. Data regarding patients’ demographics, gender, aetiology of hyperthyroidism, presence of autoantibodies, dose of RAI used an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 22 publications
1
13
4
1
Order By: Relevance
“…The subsequent logistic regression analysis also suggested that male gender was a risk factor of early hypothyroidism even accounting for other clinical factors. This is quite different with the previous studies, but we found recently a research of Malaysia also prompt that men became to hypothyroid easier than women [28]. We hypothesized that the difference may be because the genetic susceptibility among different races.…”
Section: Discussioncontrasting
confidence: 77%
“…The subsequent logistic regression analysis also suggested that male gender was a risk factor of early hypothyroidism even accounting for other clinical factors. This is quite different with the previous studies, but we found recently a research of Malaysia also prompt that men became to hypothyroid easier than women [28]. We hypothesized that the difference may be because the genetic susceptibility among different races.…”
Section: Discussioncontrasting
confidence: 77%
“…Within one year nearly 33% and by 10-and 25-year post RAI, 59%-82% developed HT. 22 While in non-immunogenic hyperthyroidism (nodules, goitre) RAI results in lower incidence of RIHT 4% after 1 year, 15% after 10 years, and 32% after 25 years. Unlike RIHT for HNC treatment in which females were at higher risk, women treated with I-131 were less likely to develop HT.…”
Section: Radioiodine (I-131) (Rai) Therapymentioning
confidence: 99%
“…Эмпирический опыт, накопленный в результате применения РЙТ в разных возрастных группах в течение 80 лет, свидетельствует в пользу эффективности данного вида лечения, в том числе при лечении гипертиреоза. В большинстве случаев достичь стойкого гипотиреоза удается в течение 6-12 месяцев после лечения радиоактивным йодом [8][9][10]. Преимуществами РЙТ являются минимальные ограничения метода даже при наличии сопутствующих заболеваний и возможность неоднократного проведения.…”
Section: Abstract: Thyrotoxicosis Radioiodine Therapy Hemoglobinopathyunclassified